Race/Ethnicity, Disability, and Medication Adherence Among Medicare Beneficiaries with Heart Failure - Zhang, Yuting; Baik, Seo Hyon (Journal of general internal medicine : JGIM, 2014)
ABSTRACT BACKGROUND Recent and national data on adherence to heart failure drugs are limited, particularly among the disabled and some small minority groups, such as Native Americans and Hispanics. OBJECTIVE We compare medication adherence among Medicare patients with heart failure, by disability status, race/ethnicity, and income. DESIGN Observational study. SETTING US Medicare Parts A, B, and D data, 5 % random sample, 2007–2009. PARTICIPANTS 149,893 elderly Medicare beneficiaries and 21,204 disabled non-elderly beneficiaries. MAIN MEASURES We examined 5 % of Medicare fee-for-service beneficiaries with heart failure in 2007–2009. The main outcome was 1-year adherence to one of three therapeutic classes: β-blockers, diuretics, and angiotensin-converting enzyme inhibitors (ACEIs)/angiotensin II receptor blockers (ARBs). Adherence was defined as having prescriptions in possession for ≥ 75 % of days. KEY RESULTS Among aged beneficiaries, 1-year adherences to at least one heart failure drug were 63 %, 57 %, 53 %, 50 %, and 52 % for Whites, Asians, Hispanics, Native Americans and Blacks, respectively; among the disabled, 1-year adherence was worse for each group: 57 %, 53 %, 48 %, 44 % and 43 % respectively. The racial/ethnic difference persisted after adjustment for age, gender, income, drug coverage, location and health status. Patterns of adherence were similar among beneficiaries on all three therapeutic classes. Among beneficiaries with close-to-full drug coverage, minorities were still less likely to adhere relative to Whites, OR = 0.61 (95 % CI 0.58–0.64) for Hispanics, OR = 0.59 (95 % CI 0.57–0.62) for Blacks and OR = 0.57 (95 % CI 0.47–0.68) for Native Americans. CONCLUSION After the implementation of Medicare Part D, adherence to heart failure drugs remains problematic, especially among disabled and minority beneficiaries, including Native Americans, Blacks, and Hispanics. Even among those with close-to-full drug coverage, racial differences remain, suggesting that policies simply relying on cost reduction cannot eliminate racial differences.